The digital city. Dream or nightmare? - Philipsen, Klaus (Müller u. Busmann, 2015)
Should cities become "smart" cites? Sure, who would want a dumb city, especially now that the Metro Region has become the dominant human form of organization? Even though their governance gets more complicated as cities get bigger and bigger, they are still comparably nimble compared to nation states.
Keywords: Stadtplanung; Stadtentwicklung; Stadtwachstum; Smart City; Governance; Integrierte Stadtentwicklung; Metropolregion